Paternalistic Leadership, Polychronicity, and Life Satisfaction of Nurses: The Role of Work-Family Conflict and Family-Work Conflict in Public Sector Hospitals - Gull, Nida; Song, Zhejie; Shi, Rui; Asghar, Muhammad; Rafique, Muhammad Asim; Liu, Yupeng (Frontiers in Psychology, 2021)
Based on the leadership literature, the present study investigates how paternalistic leadership (PL) and polychronicity (PC) affect nurses’ life satisfaction (LS), specifically in public hospitals. Moreover, the mediating role of work-family conflict (WFC) and family-work conflict (FWC) is also assessed among the relationships of PL, PC and LS. The cross-sectional study design is employed in this study due to its cost benefits and the convenience of data collection at a single point in time. A survey questionnaire is used to collect data from 226 nurses, and the PLS-SEM technique is used to investigate the proposed model. The findings of this study confirmed that paternalistic leadership (PL) and polychronicity (PC) have a positive relationship with life satisfaction (LS). Furthermore, work-family conflict (WFC) partially mediated the relationship among PL, PC, and life satisfaction (LS). Additionally, family-work conflict (FWC) partially mediated the relationship between PL and LS, the role of FWC in mediating the relationship between PC and LS has found to be insignificant. Employees with high polychronicity and those whose supervisors show paternalistic leadership behavior become more satisfied with their lives and have relatively low Work-Family Conflict and Family Work Conflict. Besides, the theoretical and practical implications have also been discussed.